Development and validation of an instrument for assessing online learning environments in tertiary education: The Online Learning Environment Survey (OLLES) - Clayton, John Francis (Curtin University, 2007)
Increasingly the perceived benefits of using networked computers, software applications and computer simulations in learning activities are being exploited at all educational levels and within all curricula areas. As web-based and online software applications such as browsers, search engines, communication tools and data-bases mature, so does educator's use of this medium for teaching and learning. How we can investigate the impact of these technologies upon the educational experiences of learners was the fundamental concept addressed by this thesis. The study reports on the design, development and validation of a web-based survey instrument for use in online learning environments in tertiary education. The thesis investigated both previous psychosocial learning environment instrument development studies and the nature of environments created by the use of information and communication technologies. The research followed a two-phased instrument development process. Phase one focused on content validity, identifying salient scales and items and piloting the instrument with a limited audience. Phase two focused on construct validity, conducting an extensive field test with a web-based form and performing statistical analysis on the online data collected. Principal components analysis, with oblique and orthogonal rotations, confirmed the structure of a 35-item 7-scale instrument. The thesis concludes by confirming the new instrument, the Online Learning Environment Survey (OLLES), will allow conclusions to be drawn about student perceptions on the interactions occurring in their online environments in an economical and efficient manner.